PENGARUH PERAN PENDETA JEMAAT UNTUK MEMPERTUMBUHKAN IMAN WARGA JEMAAT ANTAR DENOMINASI DI KOTA PEMATANGSIANTAR - Elfri Darlin Sinaga (Jurnal Theologia Forum STFT Surya Nusantara, 2020)
The low level of community faith can occur due to various factors such as: Lack of moral and religious education from parents to the children, adolescents and young people in the household, lack of moral education in schools, and less role of clergy (pastors of the congregation) carry out their responsibilities fully to the members of their congregations. The purpose of this study was to determine how much influence the role of the Church Pastors on the growth of faith of the church members among the inter-denominational congregation in Pematangsiantar city. The method used in this research is descriptive method. Data were collected by distributing questionnaires to 40 respondents representing 105 inter-denominational pastors in Pematangsiantar city. Then the data collected is analyzed and discussed. The results showed that the growth of faith of the members of the congregation (Y) can be influenced by the role of the Pastors of the Church (X). The influence of the role of the Church Pastors (X) on the growth of the faith of church members among the inter-denominational congregations in Pematangsiantar city (Y) is in a significant level. The magnitude of the influence of the role of the Church pastor (X) on the growth of faith of the church members among the inter-denominational congregations in Pematangsiantar city (Y) is 32%. The relationship between the role of the Pastor of the Church (X) with the growth of the faith of the church members among the inter-denominational congregations in Pematangsiantar city (Y) is illustrated through the linear regression equation Y = 28,978 + 0,643X. that is, for every unit to improve the role of the Church Pastor (X), the growth of the faith of the church members among the inter-denominational congregation in Pematangsiantar City (Y) will increase by 0.643 times from the present condition with a constant of 28.978.For this reason, the pastor of the church needs to improve the quality of his role, especially as a shepherd, a spiritual leader, and as a trainer to increase the growth of faith of the church members among the inter-denominational congregations in Pematangsiantarcity.